Effectiveness of physical barriers and enhanced fertilization in controlling predation on tilapia and catfish aquaculture systems by four piscivorous water bird families - Otieno, Nickson Erick; Shidavi, Erick (Frontiers in Sustainable Food Systems, 2022)
Watebirds cause substantial fish-stock losses in open aquaculture systems, particularly in developing countries where fish-ponds are smaller and predator control methods largely manual or under-resourced. This study 1) compared efficiencies of three bird-control measures for reducing predation pressure by four piscivorous waterbird families in small tilapia and catfish farms in western Kenya; and 2) distinguished bird group(s) most effectively deterred by these treatments. The measure-treatments were: coarse-grained mesh barriers; finer-grained barriers; and enhanced pond fertilization. Twelve fish-ponds were randomly sampled to assess birds’ pond-neigborhood assemblages and their predation rate responses to pond treatment effects. Pond-cover status but not type, singularly and interactively with enhanced fertilization, reduced bird encounter rates. Conversely, cover status, barrier type and fertilization each deterred bird predation but not interactively, larger birds being deterred by fertilization or barriers but smaller birds only by fine-grained barriers. These results demonstrate that using enhanced fertilization and physical barriers, can significantly reduce predation pressure on open-culture pond-fish by most piscivirous birds to mitigate economic losses incurred by farmers. However, effectiveness of measures chosen depend on target bird species’ feeding habits. The findings constribute towards diversifying predator-control methods for minimizing impacts of vertebrate predators, promoting sustainable aquaculture production and improving human nutrition.